STRATEGI PENGEMBANGAN PARIWISATA PANTAI RINDU BANGKALAN (Studi Analisis Fatwa DSN-MUI Nomor 108 Tahun 2016 Tentang Pedoman Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah) - Lina, Masaulina; Holis; Adiyono (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Madura has great tourism potential and has high opportunities to develop sharia tourism, however, some tourism in Madura, especially Rindu Beach tourism, does not yet have a full tourism development strategy, and still faces several challenges in implementing sharia principles in accordance with the DSN Fatwa MUI Number 108 of 2016. This research aims to identify and formulate a tourism development strategy for Rindu Bangkalan Beach and to find out whether sharia principles as stated in MUI Fatwa Number 108 of 2016 have been implemented. Using a qualitative approach, data was collected through in-depth interviews, observation and review of relevant documents. The research results show that Rindu Beach has a strong natural attraction, good security and promotion but still faces shortcomings in terms of artificial attractions, cultural attractions, health services, souvenirs and government support. This research also analyzes the suitability of the existing conditions of Rindu Beach with sharia tourism criteria, and designs a development model that can be a reference for local governments and local tourism actors. The resulting policy recommendations are expected to increase the attractiveness of Rindu Beach as a sustainable sharia tourism destination, provide economic benefits for local communities, and preserve religious and cultural values. Keywords: Strategy, Development, Tourism, Sharia.